2015
DOI: 10.1159/000438975
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of Routine Papanicolaou Smears for Detecting Endometrial Cancers: An Update

Abstract: Objective: The presence of degenerative endometrial debris and abnormal endometrial cells is considered to be the hint for endometrial pathology. The purpose of this study was to evaluate the efficacy of Papanicolaou (Pap) smears in detecting endometrial cancers. Study Design: There were 146 cases of endometrial cancer diagnosed at our institute in 2000-2002 and 271 in 2010-2012. Among them, 57 and 95 relevant reports of Pap smears 6 months prior to the histology diagnosis were retrieved for this study, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 13 publications
(22 reference statements)
1
22
0
Order By: Relevance
“…The value of Papanicolaou tests for detection of EC was evaluated in several retrospective studies 3,12–15 . This current research supports the findings of low sensitivity of Papanicolaou tests for detection of EC.…”
Section: Discussionsupporting
confidence: 83%
“…The value of Papanicolaou tests for detection of EC was evaluated in several retrospective studies 3,12–15 . This current research supports the findings of low sensitivity of Papanicolaou tests for detection of EC.…”
Section: Discussionsupporting
confidence: 83%
“…It is simple, inexpensive, and the required equipment is available at general hospitals. Previous studies have reported that 38-51% of endometrial cancer patients had abnormal Pap smear results and that abnormal cervical cytology was correlated with tumor size, tumor type, depth of invasion, presence of cervical involvement, and presence of lymphovascular invasion (Lai et al, 2015;Serdy et al, 2016).…”
Section: Association Of Abnormal Pap Smear With Occult Cervical Strommentioning
confidence: 97%
“…Exfoliated endometrial cells may be considered to be normal during menstruation and proliferative phases by Pap smear. However, a more comprehensive assessment should be performed if this type of cells are encountered in the postmenopausal women (8). In the literature, some studies have demonstrated that reporting endometrial cells detected in the cervical screening by Pap smear test may be significant with respect to endometrial carcinoma.…”
Section: Introductionmentioning
confidence: 99%